Leukotrienes in cerulein-induced acute pancreatitis in rats and effect of octreotide - , Galip ERSÖZ, Afik HÜSEYİNOV, Ömer ÖZÜTEMİZ, Gül YÜCE, Işıl ÇOKER, Yücel BATUR (Turkish Journal of Gastroenterology 1, 2019)
-